Critical Period of Cucumber Fruit (Cucumis sativus Linn) Against Black Fruit Bug (Leptoglossus australis F.) in the field - MONIKA, MONIKA; Dr.Ir.Tris Haris Ramadhan,MP, Dr.Ir.Tris Haris Ramadhan,MP; Ir.Indri Hendarti,M.Sc, Ir.Indri Hendarti,M.Sc (Jurnal Sains Pertanian Equator, 2019)
Monika (1), Tris Haris Ramadhan (2), Indri Hendarti( 3) (1) University Student of Agriculture and (2) Instructor Staf of Agriculture Faculty Tanjungpura University Pontianak ABSTRACTLeptoglossus australis F is one of the pests of cucumber that reduce the quality and quantity of yield. The purpose of this research was to find out when the critical period of fruit whenever attack by L.australis can cause damage. The research was conducted in the plant protection laboratory and on the land of the Faculty of Agriculture of Tanjungpura University for approximately 5 months. The design used was a randomized block design (RAK) with 7 treatment levels and 4 replications. The treatment use was time of infestation (M) when the different of fruit age began with one days post pollination (M1), two days after pollination (M2), three days after pollination (M3), four days after pollination (M4), five days after pollination (M5), and six days after pollination (M6) along with the control (M0). In each treatment was infested two bugs of 3rd instar with one day infestation. Before infestation, the bug fasting at 10 hours. The damage of cucumber fruit is measured by the length of the fruit, the diameter of the fruit, and the weight of the fruit of the cucumber. The result showed that the infestation of two bug in third instar at the age of 1 day after bloom has caused the symptoms of destruction and loss of cucumber fruit.Keywords : Cucumber, Infestation, L. australis (F), Product loss. 1) University Student of Agriculture and (2) Instructor Staf of Agriculture Faculty Tanjungpura University Pontianak